Prognostic value of GDF levels 15 and NTproBNP and echocardiographic parameters in patients with heart failure with preserved ejection fraction, after myocardial infarction on the background of hypertension according to the three-year observation - V. D. Syvolap; Ya. V. Zemlyaniy (Zaporožskij Medicinskij Žurnal)
Chronic heart failure with preserved ejection fraction refers to syndromes with a poor prognosis.